Antibiotics in the environment: causes and consequences - Polianciuc, Svetlana Iuliana; Gurzău, Anca Elena; Kiss, Bela; Ștefan, Maria Georgia; Loghin, Felicia (Medicine and Pharmacy Reports, 2020)
Antibiotics represent one of the main discoveries of the last century that changed the treatment of a large array of infections in a significant way. However, increased consumption has led to an exposure of bacterial communities and ecosystems to a large amount of antibiotic residues. This paper aims to provide a brief overview of the primary drivers associated with antibiotic occurrence in the environment. Furthermore, we attempted to summarize the behavior of antibiotic residues in the environment and the necessity of their detection and quantification. Also, we provide updated scientific and regulatory facts about environmental antibiotic discharge and environmental and human antibiotics risk assessment. We propose that environmental antibiotic contamination should be diminished beginning from regulating the causes of occurrence in the environment (such as antibiotic consumption) and ending with regulating antibiotic discharge and risk assessment. Some important intermediate steps are represented by the detection and quantification of the antibiotics and the characterization of their behavior in the environment, which could come to support future regulatory decisions.